2000
DOI: 10.1007/bf02237250
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of microscopic peritoneal dissemination

Abstract: Because microscopic peritoneal dissemination influences survival time after R0 resections only in patients with gastric but not with colon cancer, our results may provide a basis for a decision on additive, prophylactic (intraperitoneal) therapy in gastric but not colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 24 publications
5
47
2
1
Order By: Relevance
“…One such study found positive cytology for colorectal cancer cells in imprints of the peritoneal surface in 9.25% of cases (all stages) and this was correlated with death from disease in univariate (P = 0.008) and multivariate (P < 0.001) analyses (25). Vogel et al (26) showed that 35.5% (32 of 90) of patients with colon cancer had positive cytology in peritoneal lavage samples. This was significantly associated with depth of invasion of the tumor and presence of metastases but not with unfavorable prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…One such study found positive cytology for colorectal cancer cells in imprints of the peritoneal surface in 9.25% of cases (all stages) and this was correlated with death from disease in univariate (P = 0.008) and multivariate (P < 0.001) analyses (25). Vogel et al (26) showed that 35.5% (32 of 90) of patients with colon cancer had positive cytology in peritoneal lavage samples. This was significantly associated with depth of invasion of the tumor and presence of metastases but not with unfavorable prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…In the other control with sigmoidal cancer, the presence of free tumour cells was not shown. However, as previous studies have indicated, not all colonic cancers with serosal engagement lead to the presence of free cancer cells in peritoneal lavage (16). Furthermore, isolated cells of colonic epithelial origin can be detected with CK20/CDX2 and MUC2 staining as a result of exposure of the mucosa at the stapler line during rectal transection.…”
Section: Discussionmentioning
confidence: 89%
“…In advanced ovarian cancer with peritoneal dissemination, the detection rate of malignant cells in ascites has been reported to be as high as 89%, 16 and in advanced gastric cancer with peritoneal dissemination, the detection rate has ranged from 42.3-59%. 17,18 However, in advanced CRC with peritoneal dissemination, the detection rate of malignant cells in ascites, using peritoneal cytology assays, has been as low as 5. 24 used an empiric cut-off value, and Loewenstein and Zamcheck 9 reported a cut-off value for aCEA in malignant ascites of 10 ng/mL (the highest aCEA level of the benign group).…”
Section: 송성은 등 대장암 환자에서 복수내 암태아 항원의 진단적 가치mentioning
confidence: 99%